Keragaman Jenis Tumbuhan pada Berbagai Pola Agroforestri di Hutan Kemasyarakatan Aik Bual Lombok Tengah - Fikry, Muhammad Yul; Sarjan, Muhammad; Sjah, Taslim (Lembaga Bale Literasi, 2024)
This study examines the implementation of agroforestry patterns in the Community Forest of Aik Bual, Central Lombok. The Ministry of Environment and Forestry granted management rights for this forest area under the HKm scheme to local communities for 35 years, managed by the Forest Management Unit of Pelangan Tastura involving 260 farmers over 94.45 hectares of land. Agroforestry, as a sustainable land management system integrating agriculture and forestry, is the primary focus to maximize land productivity while maintaining environmental sustainability. The research was conducted from February to June 2024 using a descriptive method to depict the diversity of plant species, strata, and land utilization by farmers. Data were collected through interviews, field observations, documentation, and literature review. Diversity analysis employed indices such as Importance Value Index (IVI), Diversity Index (H'), Species Richness (K), and Relative Density (KR). Results indicated that agroforestry patterns in HKm Aik Bual significantly enhance vegetation diversity, plant structure, and diversity of understory species. Further research is needed to better understand the interaction between agroforestry patterns and plant species diversity in HKm Aik Bual. Consequently, this study's findings are expected to make a significant contribution to supporting sustainable forest management, providing optimal ecological and economic benefits to the local communities surrounding the forest area.